Keefektifan Model Grow pada Kemampuan Pengarahan Supervisor Keperawatan: Literature Review - Sasmita Dewi; Yulastri Arif; Zifriyanthi Minanda Putri; Dewi Murni (Universitas Batanghari Jambi, 2023)
The ability to direct nursing managers is very important in improving the performance of subordinates. Briefing should be carried out by an officer who has been given responsibility or who is called a supervisor. Supervisor should be responsible for the performance of staff in the process. Supervision should provide a safe and confidential environment for staff to reflect and discuss their work, which enhances their awareness and clinical skills and leads on increasing competence. Also stated that in providing education and direction a supervisor must have communication skills, psychological understanding and be a good role model. explained that the ability to direct a supervisor consists of the ability to schedule supervision including time and agenda, the ability to provide constructive feedback, the ability to collaborate, respect and provide support and the ability to Boundary or form bonds. The GROW model is one of the most widely used models in training and teaching programs.This model can be modified into the T-GROW model based on the topic of briefing to be given.Purpose: Conduct a literature review to determine the effectiveness of the T-GROW model on the supervisor's directive abilities. A literature search was carried out using the keywords GROW AND Effectiveness AND Nurse supervisor model using the prism method search engine database PubMed, ScienceDirect and Google Scholar and obtained 109 research articles and then checking the completeness of the menu on the research articles with a total of 54 articles. done the separation of criteria and the critical review stage used the Joanna Bringgs Institute (JBI) format with a total of articles that were reviewed in the literature. The ability to direct a nursing supervisor consists of five, namely the ability to communicate, the ability to set schedules, tasks and responsibilities, the ability to bind individuals, the ability to be a role model and the ability to provide feedback. The T-GROW model training is effective in improving teacher skills and behavior in providing direction and learning to students and is also effectively used in organizing leadership training. and effective in teaching, learning and supervision. The T-GROW model is effective in teaching, learning and supervision. The T-GROW model has not been widely applied in clinical services, so it is recommended that future researchers apply the T-GROW model to improve the ability to direct nursing supervisors in supervising.